Studies in fluorescence resonance energy transfer in a FAM/Iowa black labeled thrombin-binding aptamer - Blatnik, Jay (My University, 2010)
Describes a study with the hypotheses: using a dual labeled thrombin-binding aptamer (TBA), as ions are added to the solution total fluorescence will decrease when using FAM and Iowa black-FQ as a result of fluorescence resonance energy transfer (FRET).
A poster containing visuals and text describing an undergraduate research project completed at the University of Wisconsin--Whitewater.
Keywords: Fluorescence.; DNA-binding proteins; Thrombin; DNA; RNA; Cations